Vertex Magic Labeling On V_4 for Cartesian product of two cycles - et. al., Dr. V. L.Stella Arputha Mary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let be an abelian group under multiplication. Let . Then the vertex magic labeling on is induced as such that where the product is taken over all edges of incident at is constant. A graph is said to be - magic if it admits a vertex magic labeling on . In this paper, we prove that , , Generalized fish graph, Double cone graph and four Leaf Clover graph are all -magic graphs.